Metrological Dimensions in the Repair of Internal Combustion Engine Cylinders - Saidullah Khan, Akbarov; Makhliyo, Jumaeva; Botirjon, Abdullajonov; Makhmudjon, Melibaev (Miasto Przyszłości, 2023)
This article describes in detail information about the manufacture and repair of parts of internal combustion engines, ensuring metrological dimensions at the required level, types of measurements, means and rules for their use.